2022
DOI: 10.18203/2349-3259.ijct20222689
|View full text |Cite
|
Sign up to set email alerts
|

The stigma of mental health, homelessness and intellectual disability, development of a national stigma survey with an intersectional gender perspective

Abstract: <p><strong>Background:</strong> Social stigma towards people with mental health problems, homeless people or people with intellectual disabilities leads to a significant restriction of their human rights. Such stigma, which is associated with different conditions of vulnerability, has been assessed over time through surveys. However, intersectional stigma due to gender is often not assessed in these studies as they only analyse the data for this variable separately. Therefore, presented here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…This study is part of a larger research project, which was conducted in order to assess the stigma associated with different realities (homelessness, mental health problems, and intellectual disability) within the framework of the Chair Against Stigma Complutense University of Madrid-Grupo 5. The research protocol can be found in Zamorano et al (2022). The procedure and results presented in this article are those related to social stigma in the general population toward PEH.…”
Section: Methodsmentioning
confidence: 99%
“…This study is part of a larger research project, which was conducted in order to assess the stigma associated with different realities (homelessness, mental health problems, and intellectual disability) within the framework of the Chair Against Stigma Complutense University of Madrid-Grupo 5. The research protocol can be found in Zamorano et al (2022). The procedure and results presented in this article are those related to social stigma in the general population toward PEH.…”
Section: Methodsmentioning
confidence: 99%
“…First, a comprehensive review of the literature was conducted to identify assessment instruments employed in other surveys on stigma towards people with intellectual disability (McConkey et al, 2021;Pelleboer-Gunnink et al, 2021) (Zamorano et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The data were processed in accordance with Regulation (EU) 2016/679 of the European Parliament and of the Council of 27 April 2016 on the protection of personal data. This study is part of a broader research project conducted by the Chair Against Stigma UCM‐Grupo 5 to assess the stigma associated with different vulnerable populations (Zamorano et al ., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…This study is part of a broader investigation on the assessment of stigma of various conditions carried out by the Chair Against Stigma of the Complutense University of Madrid and Grupo 5 (Zamorano et al, 2022). Using a consumer panel methodology with a matched replacement (i.e.…”
Section: Methodsmentioning
confidence: 99%